(untitled) (Belas Infiéis, 2016)
This study investigates how six idioms from the TV Series Bates Motel, Season 01, Episode 06 (BMS01E06) are translated from English into Brazilian Portuguese (BP) in the official subtitles following one of Baker’s (1992) idioms translation suggestions: paraphrase. Specifically, it analyzes the meaning of such idioms in the English context compared to their meaning rendered in the BP context. The results point out that: i) the idioms may highlight the inexistence of English-Portuguese one-to-one idioms; ii) the figurativeness of the English idioms is found in different lexical items in BP paraphrases; iii) the subtitling technical constraints of time, space and presentation have been fulfilled in all cases analyzed. The conclusion reached is that culture-specific idioms can be translated in a particular context and subtitling translation may link different peoples and cultures.